2017
DOI: 10.1136/jim-2016-000176
|View full text |Cite
|
Sign up to set email alerts
|

Calcipotriol Inhibits Proliferation of Human Keratinocytes by Downregulating Stat1 and Stat3 Signaling

Abstract: Psoriasis is an autoimmune disease, which is characterized by aberrantly high levels of inflammation, but the underlying pathogenic mechanisms are still not fully understood. Signal transducer and activator of transcription 1 (STAT1) and STAT3, and the downstream proteins suppressor of cytokine signaling 1 (SOCS1) and SOCS3, have been implicated in psoriasis disease progression. Calcipotriol, a synthetic derivative of vitamin D, has been used clinically to treat psoriasis, but the mechanism of action that unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…Thus, STAT3 has been aroused as an ideal therapeutic target for psoriasis. Indeed, a recent study has shown that calcipotriol, which has been used widely for the treatment of psoriasis, inhibits proliferation of keratinocytes by downregulating phosphorylation of STAT3 [ 32 ]. Our data showed a decrease in epidermal thickness in IMQ-treated mice by topical application of PG102 as well as suppression of proliferation and phosphorylation of tyrosine 705 and serine 727 residues of STAT3 in HaCaT cells.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, STAT3 has been aroused as an ideal therapeutic target for psoriasis. Indeed, a recent study has shown that calcipotriol, which has been used widely for the treatment of psoriasis, inhibits proliferation of keratinocytes by downregulating phosphorylation of STAT3 [ 32 ]. Our data showed a decrease in epidermal thickness in IMQ-treated mice by topical application of PG102 as well as suppression of proliferation and phosphorylation of tyrosine 705 and serine 727 residues of STAT3 in HaCaT cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that STAT3 is a key transcriptional factor involved in the regulation of cell proliferation, and the inhibitions of STAT3 phosphorylation or expression can result in decreased proliferation of normal human KCs or HaCaT cells. [ 12 18 ] In our study, STAT3 siRNA inhibited the growth of psoriatic KCs in a time-dependent manner. The siRNA carried by Lipofectamine 3000 combined with ultrasonic irradiation and SonoVue microbubbles showed higher proliferation inhibition compared with that only carried by Lipofectamine 3000.…”
Section: Discussionmentioning
confidence: 51%
“…More specifically, calcipotriol affects mostly differentiation and apoptosis, whereas cPLA 2 ɑ appears to mostly affect proliferation. Calcipotriol is able to have both an antiproliferative ( Kristl et al., 2008 ; Liang et al., 2017 ) and a pro-apoptotic effect ( Huang et al, 2019 ; Tiberio et al., 2009 ) in psoriatic KCs. Apoptosis is subject to an elaborate regulation and controlled by the ratio of pro- to anti-apoptotic regulators, meaning that both types of regulators can be active at the same time ( Jan and Chaudhry, 2019 ).…”
Section: Resultsmentioning
confidence: 99%